A grave revisited. On grave robbery in Viking Age Iceland - Erna Þórarinsdóttir 1976- (2008)
A relatively large part of the graves from the Viking period in Iceland have been robbed or disturbed in some way. Until present day, this fact has not caught the interest of archaeologists working in Iceland and has therefore remained unstudied. Grave goods are the basis of research materials representing material culture from the Viking Age. It is possible that incomplete grave furniture gives the wrong picture of what objects people had in their possession during the Viking Age. It is essential that the implications of this should be taken into account in archaeological studies. This paper argues as well the necessity that reasons behind grave robbery be studied, since 1/6 of the graves found so far from the Viking Period, have been robbed.